The study of mineral elements of the herb of Aerva lanata (Linn.) Juss. ex Schult - Protska, Viktoria (Annals of Mechnikov’s Institute, 2022)
Introduction. Aerva lanata (Linn.) Juss. ex Schult belongs to Amaranthaceae Juss. family. Aerva lanata(Linn.) Juss. ex Schult is widely used in the traditional medicine of many countries of the world for the treatment of diabetes, urolithiasis, malaria, fever, hemorrhage, cough, asthma, bronchitis, hypertension, osteoporosis and for wound healing. Many researchers specify that Aerva lanata (Linn.) Juss. ex Schult display antimicrobial, antioxidant, antiviral, antiplasmodial, analgesic, astringent, diuretic, litholytic, anthelmintic, antihyperglycemic, hypolipidemic, antiasthmatic, immunomodulatory, antitumor, antidiarrheal, nephro- and hepatoprotective properties. As follows from the literature, overground parts of Aerva lanata (Linn.) Juss. ex Schult contain mainly steroid, phenolic compounds, tanins, amino acids, terpenoids and alkaloids. Its herb accumulates flavonoids (quercetin, isorhamnetin-3-O-glucoside, narcissin kaempferol and its derivates), phenolic acids (vanilinic acids, siringic acids, p-hydroxybensoic acids, p-coumaric acids and ferulic acids) and betacyanin compound which named betanin. A preliminary phytochemical analysis of the leaves and flowers of Aerva lanata (Linn.) Juss. ex Schult by Nigerian researchers showed the presence in these samples of acidic polysaccharides, phytoecdysteroids, and alkaloids (aervine, methylervine, methergine, aervoside, and aervolanine). Quinones, phlobatanins, triterpenoids (β-sitosterol, daucosterol, and phytosterol) were found in the roots of Aerva lanata (Linn.) Juss. ex Schult. Along with them, there is not enough information about the chemical composition and pharmacological action of this plant for its useful in medicine. Mineral elements are important in provision of human organism normal function. Such mineral elements as sodium and potassium are present in interstitial liquors, they support homeostasis, normalize arterial pressure. Abnormally low potassium concentration in blood plasma leads to hypokalemia and osteoporosis, increases risks of a stroke. Sodium deficit causes hyponatremia which may lead to renal and cardiac disease, provokes cerebral edema with corresponding neurological consequences. Calcium participates in nerve impulse transmissions, it is a structural component of conjunctive tissue and ensures bone strength. Copper, iron, manganese, selenium, and zinc are hormone and enzyme cofactors, participating in numerous biochemical reactions in the organism. Copper controls free radical reactions and lipid peroxidation processes. Copper deficit affects antioxidant system which leads to increase of active oxygen forms level, damage to lipids, proteins, provokes liver fatty degeneration and favors high cholesterol concentration in blood plasma. Cobalt and iodine participate in red blood cell formation. Iron as a component of hemoglobin and cytochromes supports cell respiration. Molybdenum activates antioxidant enzymes. Copper, selenium and zinc control humoral immunity and increase organism resistivity. As human organism is unable to produce mineral elements, they must be introduced with food or replenished by taking medicines. Along with that, such elements as lead, cobalt, mercury, arsenic, cadmium, etc. can accumulate in body tissues, and their excess leads to intoxication. It is a well-known fact that the ability to accumulate various elements in the growth is quite variable and depends on the surrounding conditions, so this indicator must be controlled. The purpose of the work was a study in qualitative composition and determination of quantitative content of mineral elements in herb of Aerva lanata (Linn.) Juss. ex Schult. Materials and methods. Mineral composition of Aerva lanata (Linn.) Juss. ex Schult herb was studied by atomic absorption spectroscopy. The five samples of Aerva lanata (Linn.) Juss. ex Schult herb of domestic manufacturers (LLC Klyuchi zdrovya, PrJSC Liktravy, PrJSC Pharmaceutical Factory Viola and LLC NVO PhytoBioTechnology) were used for the analysis. The raw materials were purchased in pharmacies in Kharkiv in 2021. Results and discussion. During the results of the analysis, 19 mineral elements were identified and determined in Aerva lanata (Linn.) Juss. ex Schult herb. The total content of them was 5215.21 μg/100 g. During the results of the analysis, 19 mineral elements were identified and determined in Aerva lanata (Linn.) Juss. ex Schult herb. The total content of them was 5215.21 μg/100 g. Quantitative content of identified mineral elements gradually decreased in succession K > Ca > Mg > Na > Si > Sr > Al > P > Mn > Fe > Zn > Cu > Mo > Ni. The content of macro elements in the herb of Aerva lanata (Linn.) Juss. ex Schult was 5101.20 µg/ 100 g. Potassium was the dominant macro element in Aerva lanata (Linn.) Juss. ex Schult herb. The content of it were 3020.00 µg/ 100 g. The content of calcium (785.00 μg/100 g) in the studied sample was almost 4 times less. The total content of trace elements was 114.01 μg/100 g. Strontium prevailed among trace elements (67 μg/kg). Aluminum (20.10 μg/100 g) was accumulated in this raw material almost three times less. The content of manganese (11.20 μg/ 100 g) and ferrum (9.0 μg/ 100 g) in Aerva lanata (Linn.) Juss. ex Schult herb was almost the same. In addition, a high content of zinc (6.20 µg/100 g) was noted in the studied sample. The content of heavy metals in Aerva lanata (Linn.) Juss. ex Schult herb met the requirements of State Pharmacopoeia of Ukrainian, never exceeding acceptable limits for medicinal herb. Key words: Aerva lanata (Linn.) Juss. ex Schult, Amaranthaceae Juss., atomic absorption spectroscopy, mineral elements.